2003
DOI: 10.1034/j.1600-0609.2003.00039.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoproliferative disease of granular lymphocytes with T‐cell receptor gamma delta‐positive phenotype: restricted usage of T‐cell receptor gamma and delta subunit genes

Abstract: Lymphoproliferative disease of granular lymphocytes (LDGL) is characterized by more than 0.5 x 109/L of proliferating granular lymphocytes in the peripheral blood. Because of its rarity, the characteristics of LDGL with T-cell receptor (TCR) gammadelta phenotype (gammadeltaT-LDGL) have not yet been identified. This report describes the clinical, hematological, and immunological findings of four patients with this disease. In two cases, the clinical course was indolent and the other two patients required variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…Because gamma delta T-cell LGL leukemia is rare, we reviewed the literature for other cases with adequate immunophenotypic data for comparison ( Table 2). The immunophenotypic data reported here are similar to those in the literature (10,(13)(14)(15). CD2 and CD3 were positive and CD4 negative.…”
Section: Gamma Delta T-cell Lgl Leukemiasupporting
confidence: 79%
See 4 more Smart Citations
“…Because gamma delta T-cell LGL leukemia is rare, we reviewed the literature for other cases with adequate immunophenotypic data for comparison ( Table 2). The immunophenotypic data reported here are similar to those in the literature (10,(13)(14)(15). CD2 and CD3 were positive and CD4 negative.…”
Section: Gamma Delta T-cell Lgl Leukemiasupporting
confidence: 79%
“…However, gamma delta T-cell LGL leukemias have a very indolent clinical course with symptoms (increased and recurrent infections) primarily resulting from neutropenia and not from the gamma delta T-cell process. Patients with gamma delta T-cell LGL leukemia in the present study and in the literature demonstrated good survival despite receiving minimal therapy, such as cyclosporin, or no therapy (13)(14)(15). The more aggressive and more common gamma delta T-cell hepatosplenic lymphoma has frequent involvement of bone marrow (72% of cases) and peripheral blood (50% of cases) and, similar to gamma delta T-cell LGL leukemias, can present initially with abnormal peripheral blood findings (3)(4)(5).…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations